The Influence Of Price, Promotion And Product Innovation On Customer Satisfaction At PT. Djarum Makassar - Makkira -; M. Syakir -; Febrizul Akbar (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
For 150-200 word, An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by di. scipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper. Keywords: content; formatting; article.